Antimicrobial Efficacy of Mineral Trioxide Aggregate with and without Silver Nanoparticles - Samiei, Mohammad; Aghazadeh, Mohammad; Lotfi, Mehrdad; Shakoei, Sahar; Aghazadeh, Zahra; Vahid Pakdel, Seyyed Mahdi (Iranian Endodontic Journal, 2013)
Introduction: Most current root-end filling materials do not provide a perfect seal. Thus, a microscopic space is likely to exist in the interface between walls of the root-end cavity and filling material, which allows microorganisms and their products to penetrate. In addition to good sealing ability and biocompatibility, root-end filling materials should ideally have some antimicrobial activity. Therefore, this in vitro study aimed to evaluate the antimicrobial properties of Angelus white mineral trioxide aggregate (MTA) and the mixture of MTA with silver nanoparticles (1% weight; MTA/SN). Materials and Methods: Antimicrobial properties of MTA and MTA/SN were tested by agar diffusion technique against Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans. The microbial inhibition zones around the materials were measured by a caliper with 0.1-mm accuracy. Student’s t-test was used for comparison between the two groups in normal data distribution and Man-Whitney U test for non-normal distribution. Results: Student’s t-test revealed that for E. faecalis, C. albicans, and P. aeruginosa, microbial inhibition zone of MTA/SN was significantly greater than that of MTA (P=0.000). Mann-Whitney U test indicated no significant difference between the effect of MTA and MTA/SN on S. aureus (P>0.05). Conclusion: Based on the results of this study, adding silver nanoparticles to MTA improved its antimicrobial efficacy.